EFFECTIVENESS OF THE LET’S GENERATE ELECTRICITY FROM THE SUN PROGRAM IN PROMOTING INTEREST AND UNDERSTANDING IN STEM EDUCATION - Muhammad, Nurmalessa; Mohamed, Syafawati Nadiah; Zainuddin, Hedzlin; Mohamed, Zakiah; Kamisan, Ainnur-Sherene; Mohd Nor, Asiah; Jaafar, Nor Kartini (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The increasing demand for renewable energy underscores the need for early education to foster awareness and interest among younger generations. This study evaluates the effectiveness of the “Jom Jana Elektrik Dari Matahari” program in enhancing students’ knowledge of photovoltaic (PV) systems, interest in science, technology, engineering, and mathematics (STEM), and attitudes toward renewable energy. A quantitative pre-test–post-test research design was employed involving 100 participants. Data were analysed using paired-sample t-tests and Cohen’s d effect size measures. The findings indicate statistically significant improvements across all measured domains, demonstrating the effectiveness of experiential sustainability-focused interventions in promoting STEM engagement and environmental awareness. A total of 72% indicated readiness to join community-based projects and preferred hands-on learning such as solar kit workshops and field visits. Post-program evaluation demonstrated substantial improvements: 99% of students reported increased interest in science, 100% showed enhanced understanding of photovoltaic systems, 98% displayed greater awareness of solar energy’s environmental benefits, and 96% improved their understanding of eco-friendly lifestyle practices. These results confirm that structured, contextualized learning—combining lectures, practical sessions, and interactive discussions—is effective in strengthening both cognitive and attitudinal outcomes. The program successfully boosted students’ engagement with STEM while promoting sustainability awareness, aligning with Malaysia’s green energy aspirations. The study concludes that university–community collaborations are valuable platforms for advancing renewable energy education and recommends expanding similar initiatives through curriculum integration and long-term follow-up studies.